2006
DOI: 10.1007/s00383-006-1650-7
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative angiography with embolization and radiofrequency ablation as novel adjuncts to safe surgical resection of a large, vascular sacrococcygeal teratoma

Abstract: Sacrococcygeal teratomas (SCTs) can present a challenging problem and can be associated with significant perinatal morbidity and mortality. A female child was born at 36 weeks' gestation with a large, vascular Type 1 SCT originally identified by prenatal ultrasound. A CT scan showed two large feeding vessels arising from both internal iliac arteries that were successfully embolized during angiography. A radiofrequency probe was then used to ablate a zone between normal tissue and the tumor. The SCT was subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Postnatal adjuncts to surgical tumor resection include laparoscopic ligation of the median sacral artery or preoperative angiography with embolization of the tumor vessels [18][19][20][21][22][23][24][25]. The TFR may help identify fetuses at risk for poor outcome that may benefit from close monitoring for the onset of hydrops.…”
Section: Discussionmentioning
confidence: 98%
“…Postnatal adjuncts to surgical tumor resection include laparoscopic ligation of the median sacral artery or preoperative angiography with embolization of the tumor vessels [18][19][20][21][22][23][24][25]. The TFR may help identify fetuses at risk for poor outcome that may benefit from close monitoring for the onset of hydrops.…”
Section: Discussionmentioning
confidence: 98%
“…The origin and number of the feeding arteries are well identified by arteriography, which also allows embolization of the arteries. This method of preoperative embolization of SCT was first described by Cowles and al [5]. Their patient was born at 36 weeks' gestation, and the SCT weighed 1335 g. The risk of fatal heart complication was further increased in our case.…”
Section: Discussionmentioning
confidence: 81%
“…Reaching and identifying the feeding artery may be problematic and lead to fatal bleeding. To reduce bleeding during the operation, Cowles et al [5] reported a successful preoperative angiographic embolization and radiofrequency ablation of a SCT in a girl born at 36 weeks' gestation. We present a case of a premature neonate with a very large SCT and pulmonary problems, whose tumor was successfully embolized via angiographic intervention before the operation.…”
mentioning
confidence: 98%
“…The tumor was separated from the conus medullaris and cauda equina and was reflected inferiorly toward its connection with the sacral extradural portion of the lesion. described elsewhere and resulted in excellent hemostasis during SCT resection [30,31]. In our patient, we cautiously used a delayed resection strategy after embolization because of the long duration (4 hours) required for angiography with vessel occlusion as well as the desire to treat the neonate's hypervolemic state before engaging in a long and arduous operation.…”
Section: Discussionmentioning
confidence: 92%